2020
DOI: 10.1007/s42452-020-2133-5
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable approach towards utilizing Makrana marble waste for making water resistant green composite materials

Abstract: During marble mining, processing, cutting and polishing, more than 12 MT (million tons) of marble waste is produced in the state of Rajasthan, India, which is now a major environmental issue. The marble waste used in the present study was collected from Makrana marble mining, Rajasthan. The major mineral present in marble waste were calcite (CaCO 3), dolomite (CaMg(CO 3) 2) and quartz (SiO 2). Composite materials were made using marble waste with epoxy resin. Textile fibres such as jute, cotton and glass fibre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…[18] Alternative materials made from solid wastes can be a cost-effective solution and have a large market potential to meet the demand of society. [19,20] Studies have demonstrated the utilization of marble waste as a substitute for natural sand in concrete, [21] as a part replacement in cement, [22] as a filler in polymer matrix composite, [23,24] in geopolymer based bricks, [25] in ceramic composite bricks [26] and in low-density polyethylene for the application in electrical insulating material. [27] Very limited literature has been found on the utilization of marble waste in PVC.…”
Section: Introductionmentioning
confidence: 99%
“…[18] Alternative materials made from solid wastes can be a cost-effective solution and have a large market potential to meet the demand of society. [19,20] Studies have demonstrated the utilization of marble waste as a substitute for natural sand in concrete, [21] as a part replacement in cement, [22] as a filler in polymer matrix composite, [23,24] in geopolymer based bricks, [25] in ceramic composite bricks [26] and in low-density polyethylene for the application in electrical insulating material. [27] Very limited literature has been found on the utilization of marble waste in PVC.…”
Section: Introductionmentioning
confidence: 99%
“…About 200 million tons of marble waste by marble processing industries, as a waste powder or sludge, has been produced worldwide. About 16 million tons of this waste has been created in India alone annually [ 5 , 6 , 7 , 8 ]. These marble processing industries involve mines and processing units for manufacturing tiles, blocks, decorative articles, waste disposal areas, and other activities [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Marble waste particulates in a polypropylene matrix with wood particulates [ 1 ] and magnesium hydroxide for making flame retardant composite material [ 36 ] were also analyzed. Polymer composites were fabricated using waste marble particulates with unsaturated polyester resin [ 37 ], epoxy resin [ 7 , 38 ], and polypropylene matrix [ 9 ]. However, as per the authors’ best knowledge, very few works have been reported on the use of marble waste particulates (MPs) as filler in polypropylene (PP) composites by the injection molding (at different temperatures) technique and their physical and mechanical characterization.…”
Section: Introductionmentioning
confidence: 99%
“…Each stage produces a considerable amount of waste, which, in the absence of a comprehensive waste management system, is typically disposed in open landfill sites 15 . Around 16 million tons of marble waste are produced annually in India, and lack of proper handling of this industrial byproduct has seriously harmed the local ecosystem 18 . Marble waste has found its application in making composites with enhanced properties, 18–20 bricks 21 and concrete 22 but it's utilization in poly(vinyl chloride) is still somewhat limited.…”
Section: Introductionmentioning
confidence: 99%